The Validation of the ‘CARe Burn Scale: Parent/Caregiver Form’—A Patient Reported Outcome Measure (PROM) Using Rasch Measurement Theory (RMT) to Assess Quality of Life for Parents or Caregivers Supporting a Child with a Burn Injury - Catrin Griffiths; Timothy Pickles; Ella Guest; Diana Harcourt (European Burn Journal, 2025)
A PROM is a measure of patient needs and therapeutic progress. This paper outlines the validation of the CARe Burn Scale: Parent/Caregiver Form, a PROM that measures quality of life in parents/caregivers supporting a child with a burn injury. A literature review and interviews with sixteen parents and six burns health professionals informed the development of the PROM conceptual framework/draft form. Cognitive debriefing interviews with five parents and seven burns-specialist health professionals provided feedback to ascertain content validity, and two-hundred and four parents/caregivers took part in the field testing. Rasch measurement theory (RMT) analyses and internal consistency tests were conducted to create a shortened version and for psychometric validation. The final conceptual framework included eight domains/individual scales: Physical Well-being, Confidence with Managing Burn Wound/Scar Treatments, Social Situations, Partner Relationship, Self-worth, Negative Mood, Parent Concerns about the Appearance of their Child’s Burn Wounds/Scars, and Positive Growth. Seven scales had solutions from RMT analyses and passed internal consistency criteria. Confidence with Managing Burn Wound/Scar Treatments did not fit the Rasch model but was retained as a checklist based on theoretical insight. The CARe Burn Scale: Parent/Caregiver Form is the first and only burn-specific PROM that assesses parents’ own health needs when caring for a child with a burn.